Olahraga Sehat (Jalan Santai) - Defri, Prayoga; martiani, Mariani (LPPM Universitas Dehasen Bengkulu, 2024)
This report aims to foster the spirit of healthy sports (leisurely walks) in the Pangkalan Village Community. The implementation time of this activity was carried out from November 18 to December 18, 2023. The